Magnetic resonance imaging of third molars: developing a protocol suitable for forensic age estimation - Jannick De Tobel; Elke Hillewig; Stephanie Bogaert; Karel Deblaere; Koenraad Verstraete (Taylor & Francis Group, 2017)
Background: Established dental age estimation methods in sub-adults study the development of third molar root apices on radiographs. In living individuals, however, avoiding ionising radiation is expedient. Studying dental development with magnetic resonance imaging complies with this requirement, adding the advantage of imaging in three dimensions. Aim: To elaborate the development of an MRI protocol to visualise all third molars for forensic age estimation, with particular attention to the development of the root apex. Subjects and methods: Ex vivo scans of porcine jaws and in vivo scans of 10 volunteers aged 17-25 years were performed to select adequate sequences. Studied parameters were T1 vs T2 weighting, ultrashort echo time (UTE), fat suppression, in plane resolution, slice thickness, 3D imaging, signal-to-noise ratio, and acquisition time. A bilateral four-channel flexible surface coil was used. Two observers evaluated the suitability of the images. Results: T2-weighted images were preferred to T1-weighted images. To clearly distinguish root apices in (almost) fully developed third molars an in plane resolution of 0.33 × 0.33 mm2 was deemed necessary. Taking acquisition time limits into account, only a T2 FSE sequence with slice thickness of 2 mm generated images with sufficient resolution and contrast. UTE, thinner slice T2 FSE and T2 3D FSE sequences could not generate the desired resolution within 6.5 minutes. Conclusion: Three Tesla MRI of the third molars is a feasible technique for forensic age estimation, in which a T2 FSE sequence can provide the desired in plane resolution within a clinically acceptable acquisition time.